2017
DOI: 10.1007/s11745-017-4289-3
|View full text |Cite
|
Sign up to set email alerts
|

Elongation of very Long‐Chain (>C24) Fatty Acids in Clarias gariepinus: Cloning, Functional Characterization and Tissue Expression of elovl4 Elongases

Abstract: Elongation of very long-chain fatty acid 4 (Elovl4) proteins participate in the biosynthesis of very long-chain (>C24) saturated and polyunsaturated fatty acids (FA). Previous studies have shown that fish possess two different forms of Elovl4, termed Elovl4a and Elovl4b. The present study aimed to characterize both molecularly and functionally two elovl4 cDNA from the African catfish Clarias gariepinus. The results confirmed that C. gariepinus possessed two elovl4-like elongases with high homology to two previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 36 publications
15
37
0
Order By: Relevance
“…As we have demonstrated here that ballan wrasse Elovl5 is not able to elongate 22:5n-3 to 24:5n-3, and the genome assembly available for ballan wrasse confirmed the lack of an elovl2, another mechanism would be required for the provision of the 24:5n-3 required for the Sprecher pathway. This will likely be via elongation of 22:5n-3 by Elovl4, enzymes that can be identified in ballan wrasse genomic and transcriptomic databases (data not shown), and that have been demonstrated to be capable of elongating 22:5n-3 in all fish species investigated (Monroig et al, 2010;Jin et al, 2017;Oboh et al, 2017b). Since the ballan wrasse Fads2 characterised herein did not show Δ4 desaturase capability, it can be deduced that DHA biosynthesis in ballan wrasse can only occur through the Sprecher pathway.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…As we have demonstrated here that ballan wrasse Elovl5 is not able to elongate 22:5n-3 to 24:5n-3, and the genome assembly available for ballan wrasse confirmed the lack of an elovl2, another mechanism would be required for the provision of the 24:5n-3 required for the Sprecher pathway. This will likely be via elongation of 22:5n-3 by Elovl4, enzymes that can be identified in ballan wrasse genomic and transcriptomic databases (data not shown), and that have been demonstrated to be capable of elongating 22:5n-3 in all fish species investigated (Monroig et al, 2010;Jin et al, 2017;Oboh et al, 2017b). Since the ballan wrasse Fads2 characterised herein did not show Δ4 desaturase capability, it can be deduced that DHA biosynthesis in ballan wrasse can only occur through the Sprecher pathway.…”
Section: Discussionmentioning
confidence: 78%
“…Importantly, the elovl2 gene has been lost during the evolution of teleosts and, as a consequence, the vast majority of marine fish species currently farmed do not possess this type of elongase (Castro et al, 2016). It has been postulated that loss of elongation capacity towards C 22 PUFA through the absence of Elovl2 in marine fish can be partly compensated by another elongase, Elovl4 (Monroig et al, 2010;2011) since, in addition to the biosynthesis of very long-chain (> C 24 ) PUFA (Oboh et al, 2017b), fish Elovl4 can elongate C 22 PUFA (Monroig et al, 2010;Jin et al, 2017). The above mentioned diversity of gene complement and substrate specificities in fish LC-PUFA biosynthesising enzymes demonstrates that species-specific studies on Fads and Elovl are required to unequivocally elucidate the capacity to utilise dietary VO of new fish species that are candidates for aquaculture diversification.…”
Section: Introductionmentioning
confidence: 99%
“…The results agree with the previous studies reported that additional of high HUFA such as linoleic (LOA, 18:2n–6), linolenic (LNA, 18:3n–3), eicosapentaenoic acid (EPA, 20:5n–3) or docosahexaenoic acid (DHA, 22:6n–3) in diet could promote the growth (Glencross, Smith, Thomas, & Williams, 2002a, 2002b). Interestingly, elovl4 that synthesizes very long-chain (>C24) saturated and polyunsaturated fatty acids (Oboh, Navarro, Tocher, & Monroig, 2017) was expressed at a higher level in the slow-growing shrimp than in the fast-growing one. In gilthead sea bream Sparus aurata , high amount of LNA and long-chain fatty acid adversely affected growth (Turkmen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…While majority of the studies on aquaculture candidate species focused on Elovl5 and Elovl2, studies on Elovl4 in a wide number of species have recently began to emerge (Betancor et al, 2020; Carmona‐Antonanzas et al., 2011; Jin, Monroig, Navarro, Tocher, & Zhou, 2017; Kabeya et al., 2015; Li, Monroig, Navarro, et al, 2017; Li, Monroig, Navarro, et al, 2017; Monroig et al., 2012; Monroig, Webb, et al, 2011; Oboh, Navarro‐Guillén, Tocher, & Monroig, 2017; Zhao et al, 2019). Collective, these results indicate that while both the mammalian and teleost Elovl4 play a role in the elongation of very long‐chain fatty acids (VLC‐FA) such as > C24 SFA and PUFA, the teleost Elovl4 could also catalyse the elongation of C22 PUFA substrates to C24 products, (Agbaga et al., 2008; Castro, Tocher, & Monroig, 2016; Monroig, Zheng, et al, 2010).…”
Section: Discussionmentioning
confidence: 99%